Is adherence to antiretroviral therapy by recipients of HIV care and treatment receiving care in Akwa Ibom state, Nigeria determined by their behaviors? A cross-sectional study - Usanga, Ime; Oladigbolu, Remi Abiola; Xavier, Emem; Akpenna, Donald; Daniel, Usen; Akinjeji, Adewale; Esu, Irene; Anyanwu, Prince Obinna; Peter, Abah Ehiowoicho; Immanuel, Chinyerem; Adedokun, Adetunji; Nnanna, Valentine Nnamdi; et al. (International Journal Of Community Medicine And Public Health, 2023)
Background: There has been limited use of stage of change model in scaling up self-care for optimal adherence to ART. The study aimed to assess the pattern of behavior and its associated factors among recipients of care (RoC) receiving treatment in Akwa Ibom state, Nigeria. Methods: A descriptive cross-sectional study was conducted among 423 RoC between August and October 2022. The pattern of behavior of RoC was determined using descriptive statistics, and factors associated with behavior were assessed using chi-square analysis and subsequently binary logistic regression at an alpha level of <0.05 at a 95% confidence interval using SPSS version 25. Results: Out of 423 recipients on care interviewed, 85% were in maintenance phase, and 13% in action phase. The correlates of behaviors of RoC were HIV diagnosis and on ART for over a year (p<0.001), residing in rural settings (p<0.001), and those in clinically stable DSD models (p<0.001). Over 87% of those in maintenance phase were adherent to ART, however, this was not statistically significant (p=0.21). Conclusions: Almost all the RoC were in good behavior and majority of them were adherent to ART. The factors associated with behavior of recipients of care were those diagnosed and on ART for over a year, residing in rural settings, and those in clinically stable differentiated service delivery (DSD) models. Interventions that utilize stage of change model to scale up the self-care of RoC particularly among those in the urban settings is highly imperative.